Investigation of Insomnia Among Students At The University Level: A Cross-Sectional Analysis - Fatima, Fozia; Ali, Sabir; Qamar, Khadija; Bibi, Safia; Fatima, Sobia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To investigate the students’ perception of insomnia at the university level and to determine the effects of demographic factors on their perception.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Education and Department of English, International Islamic University, from Sept 2020 to Feb 2021.Methodology: This study involved twelve hundred and fifty (1250) university students. The insomnia questionnaire was developed after the exploratory factor analysis.Results: The findings of this study revealed that students at the university level suffer from a high rate of insomnia, but they did not take any steps to address it because they had a neutral perception toward the problem. There was no significant effect of semester-term and the type of department with insomnia (p=0.864 and p=0.648).Conclusion: Students were neutral about their insomnia problem at the university level.